Comparison of the catalytic activity for the Suzuki–Miyaura reaction of (η5-Cp)Pd(IPr)Cl with (η3-cinnamyl)Pd(IPr)(Cl) and (η3-1-t-Bu-indenyl)Pd(IPr)(Cl) - Melvin, Patrick R.; Hazari, Nilay; Lant, Hannah M. C.; Peczak, Ian L.; Shah, Hemali P. (Beilstein Journal of Organic Chemistry, 2015)
Complexes of the type (η3-allyl)Pd(L)(Cl) and (η3-indenyl)Pd(L)(Cl) are highly active precatalysts for the Suzuki–Miyaura reaction. Even though allyl and indenyl ligands are similar to cyclopentadienyl (Cp) ligands, there have been no detailed comparative studies exploring the activity of precatalysts of the type (η5-Cp)Pd(L)(Cl) for Suzuki–Miyaura reactions. Here, we compare the catalytic activity of (η5-Cp)Pd(IPr)(Cl) (IPr = 1,3-bis(2,6-diisopropylphenyl)-1,3-dihydro-2H-imidazol-2-ylidene, Cp) with two commercially available catalysts (η3-cinnamyl)Pd(IPr)(Cl) (Cin) and (η3-1-t-Bu-indenyl)Pd(IPr)(Cl) (tBuInd). We show that Cp gives slightly better catalytic activity than Cin, but significantly inferior activity than tBuInd. This order of activity is rationalized by comparing the rates at which the precatalysts are activated to the monoligated Pd(0) active species along with the tendency of the starting precatalysts to comproportionate with monoligated Pd(0) to form inactive Pd(I) dimers. As part of this work the Cp supported Pd(I) dimer (μ-Cp)(μ-Cl)Pd2(IPr)2 (CpDim) was synthesized and crystallographically characterized. It does not readily disproportionate to form monoligated Pd(0) and consequently CpDim is a poor catalyst for the Suzuki–Miyaura reaction.
Keywords: cross-coupling; homogeneous catalysis; NHC ligands; palladium; Suzuki–Miyaura reaction

(untitled) - Miyaura, N.; Suzuki, A. (Chem. Rev., 1995)

(untitled) - Kotha, S.; Lahiri, K.; Kashinath, D. (Tetrahedron, 2002)

(untitled) - Phan, N. T. S.; Van Der Sluys, M.; Jones, C. W. (Adv. Synth. Catal., 2006)

(untitled) - Martin, R.; Buchwald, S. L. (Acc. Chem. Res., 2008)

(untitled) - Roughley, S. D.; Jordan, A. M. (J. Med. Chem., 2011)

(untitled) - Johansson Seechurn, C. C. C.; Kitching, M. O.; Colacot, T. J.; Snieckus, V. (Angew. Chem., Int. Ed., 2012)

(untitled) - Li, H.; Johansson Seechurn, C. C. C.; Colacot, T. J. (ACS Catal., 2012)

(untitled) - Viciu, M. S.; Germaneau, R. F.; Navarro-Fernandez, O.; Stevens, E. D.; Nolan, S. P. (Organometallics, 2002)

(untitled) - Navarro, O.; Kaur, H.; Mahjoor, P.; Nolan, S. P. (J. Org. Chem., 2004)

(untitled) - Navarro, O.; Oonishi, Y.; Kelly, R. A.; Stevens, E. D.; Briel, O.; Nolan, S. P. (J. Organomet. Chem., 2004)

(untitled) - Marion, N.; Navarro, O.; Mei, J.; Stevens, E. D.; Scott, N. M.; Nolan, S. P. (J. Am. Chem. Soc., 2006)

(untitled) - Marion, N.; Nolan, S. P. (Acc. Chem. Res., 2008)

(untitled) - Hruszkewycz, D. P.; Balcells, D.; Guard, L. M.; Hazari, N.; Tilset, M. (J. Am. Chem. Soc., 2014)

(untitled) - Hruszkewycz, D. P.; Guard, L. M.; Balcells, D.; Feldman, N.; Hazari, N.; Tilset, M. (Organometallics, 2015)

(untitled) - Melvin, P. R.; Nova, A.; Balcells, D.; Dai, W.; Hazari, N.; Hruszkewycz, D. P.; Shah, H. P.; Tudge, M. T. (ACS Catal., 2015)

(untitled) - Melvin, P. R.; Balcells, D.; Hazari, N.; Nova, A. (ACS Catal., 2015)

The Organometallic Chemistry of the Transition Metals - Crabtree, R. H. (Wiley, 2009)

(untitled) - Jin, Z.; Guo, S.-X.; Gu, X.-P.; Qiu, L.-L.; Song, H.-B.; Fang, J.-X. (Adv. Synth. Catal., 2009)

(untitled) - Jin, Z.; Gu, X.-P.; Qiu, L.-L.; Wu, G.-P.; Song, H.-B.; Fang, J.-X. (J. Organomet. Chem., 2011)

(untitled) - Jackstell, R.; Harkal, S.; Jiao, H.; Spannenberg, A.; Borgmann, C.; Röttger, D.; Nierlich, F.; Elliot, M.; Niven, S.; Cavell, K.; Navarro, O.; Viciu, M. S.; et al. (Chem. – Eur. J., 2004)

(untitled) - Werner, H.; Tune, D.; Parker, G.; Krüger, C.; Brauer, D. J. (Angew. Chem., Int. Ed. Engl., 1975)

(untitled) - Ducruix, A.; Felkin, H.; Pascard, C.; Turner, G. K. (J. Chem. Soc., Chem. Commun., 1975)

(untitled) - Werner, H.; Kühn, A.; Tune, D. J.; Krueger, C.; Brauer, D. J.; Sekutowski, J. C.; Tsay, Y.-H. (Chem. Ber., 1977)

(untitled) - Kühn, A.; Werner, H. (J. Organomet. Chem., 1979)

(untitled) - Werner, H.; Kraus, H.-J. (Angew. Chem., Int. Ed. Engl., 1979)

(untitled) - Werner, H.; Kraus, H.-J. (J. Chem. Soc., Chem. Commun., 1979)

(untitled) - Yamamoto, T.; Saito, O.; Yamamoto, A. (J. Am. Chem. Soc., 1981)

(untitled) - Werner, H.; Kraus, H.-J.; Schubert, U.; Ackermann, K. (Chem. Ber., 1982)

(untitled) - Kühn, A.; Burschka, C.; Werner, H. (Organometallics, 1982)

(untitled) - Thometzek, P.; Zenkert, K.; Werner, H. (Angew. Chem., Int. Ed. Engl., 1985)

(untitled) - Werner, H.; Thometzek, P.; Zenkert, K.; Goddard, R.; Kraus, H.-J. (Chem. Ber., 1987)

(untitled) - Tanase, T.; Nomura, T.; Yamamoto, Y.; Kobayashi, K. (J. Organomet. Chem., 1991)

(untitled) - Tanase, T.; Nomura, T.; Fukushima, T.; Yamamoto, Y.; Kobayashi, K. (Inorg. Chem., 1993)

(untitled) - Sui-Seng, C.; Enright, G. D.; Zargarian, D. (J. Am. Chem. Soc., 2006)

(untitled) - Norton, D. M.; Mitchell, E. A.; Botros, N. R.; Jessop, P. G.; Baird, M. C. (J. Org. Chem., 2009)

(untitled) - Chalkley, M. J.; Guard, L. M.; Hazari, N.; Hofmann, P.; Hruszkewycz, D. P.; Schmeier, T. J.; Takase, M. K. (Organometallics, 2013)

(untitled) - Dai, W.; Chalkley, M. J.; Brudvig, G. W.; Hazari, N.; Melvin, P. R.; Pokhrel, R.; Takase, M. K. (Organometallics, 2013)

(untitled) - Bielinski, E. A.; Dai, W.; Guard, L. M.; Hazari, N.; Takase, M. K. (Organometallics, 2013)

(untitled) - Hruszkewycz, D. P.; Wu, J.; Hazari, N.; Incarvito, C. D. (J. Am. Chem. Soc., 2011)

(untitled) - Dolomanov, O. V.; Bourhis, L. J.; Gildea, R. J.; Howard, J. A. K.; Puschmann, H. (J. Appl. Crystallogr., 2009)

(untitled) - Sheldrick, G. (Acta Crystallogr., Sect. A: Found. Crystallogr., 2008)